2020
DOI: 10.1159/000514031
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Controlling Nutritional Status plus Tumor Burden Score for the Assessment of Prognosis after Curative Liver Resection for Hepatocellular Carcinoma

Abstract: Objective: There is no prior study analyzing the prognostic predictive value of adding the tumor factor (i.e., tumor burden score) to the Controlling Nutritional Status (CONUT) score for patients with hepatocellular carcinoma (HCC). This study aimed to investigate the value of the CONUT plus Tumor Burden (CONUT-TB) score as a prognostic predictor in patients with HCC undergoing liver resection. Methods: Between 2015 and 2018, 96 consecutive patients with HCC underwent liver resection at our institution. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…42 ASA grade 3 is de ned as severe systemic disease (https://www.asahq.org/standardsand-guidelines/asa-physical-status-classi cation-system). Furthermore, poor nutritional status 15 and inadequate liver function reserve (i.e., the presence of CSPH or CP class B) 43 were associated with poor outcomes in patients with HCC undergoing LR. We thought that these prognostic factors would not be clinically relevant today.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 ASA grade 3 is de ned as severe systemic disease (https://www.asahq.org/standardsand-guidelines/asa-physical-status-classi cation-system). Furthermore, poor nutritional status 15 and inadequate liver function reserve (i.e., the presence of CSPH or CP class B) 43 were associated with poor outcomes in patients with HCC undergoing LR. We thought that these prognostic factors would not be clinically relevant today.…”
Section: Discussionmentioning
confidence: 99%
“…9 The TBS is simple to use, and numerous studies have shown its predictive value in prognosing patients with HCC undergoing LR. [10][11][12][13][14][15][16][17][18][19][20][21] Of these studies, Lima et al developed a preoperative model comprising radiographic TBS, AFP, and Child − Pugh (CP) classi cation. This model was superior to the BCLC staging system in predicting OS and further strati ed patients within each BCLC stage relative to OS.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that nutritional status is an important factor determining prognosis in malignant tumours (10,27,28) . The CONUT score focuses on the nutritional status of patients, which is a new prognostic scoring system for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the TBS was an accurate tool to predict the OS of patients with colorectal liver metastasis undergoing resection. The TBS is simple to use, and previous studies have demonstrated its impact in resected and non-resected HCC cases [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%